Lembaga Pemberdayaan Masyarakat Desa (LPMD) Dalam Penerimaan Bantuan Desa - Arum, Fitri Atur (UIN Sunan Kalijaga Yogyakarta, 2022)
Abstract: The Village Community Empowerment Institution (LPMD) is one of the Village community institutions as partners of the Village Government as stated in the Bantul Regency Regional Regulation No. 4 of 2009 concerning Village Community Institutions. In the Regional Regulation of Bantul Regency No. 4 of 2009 concerning Village Community Institutions in Article 7 paragraph (1). Based on the description above, the writer chose the title